Immune Response in Severe Infection: Could Life-Saving Drugs Be Potentially Harmful? - Maja Surbatovic; Jasna Jevdjic; Milic Veljovic; Nada Popovic; Dragan Djordjevic; Sonja Radakovic (The Scientific World Journal)
Critically ill patients suffer a high rate of nosocomial infection with secondary sepsis being a common cause of death. Usage of antibiotics and catecholamines is often necessary, but it can compromise complex immune response to infection. This review explores influence of these life-saving drugs on host immune response to severe infection.